(untitled) (Itinera, 2017)
Sound perception plays an important role in the individuation process, both in the womb and as the sense most directly linked to the speech act. The presence of mechanized noise in urban environments has been criticized both by ecological modernists and adherents of information theory’s emphasis on clear signals and the elimination of noise. This essay rejects these forms of utopianism, as they do not address the quotidian reality of the individual dealing with human resource enforced employee efficiency. Instead a form of individuation enacted by the speech act in a group setting is embraced as an aesthetic form enhanced by the technological sublime, where the presence of noise is a catalyst for remapping quotidian behaviour.